Factors Affecting Decreasing Patient Visits at Ob-Gyn Polyclinic of Outpatient Installation of “X” Hospital - Suryandewi, Made Ayu Cintya; Dwi Harjayanti, Nofita; Seyijowati, Nanik (Jurnal Kedokteran Brawijaya, 2024)
In early 2020, the SARS-CoV-2 or Covid-19 outbreak resulted in decreasing number of patient visits at “X” Hospital. “X” Hospital has set a target of health services in the outpatient installation as many as 5,500 patient visits per month, but the 2020/2021 data showed a downward trend in patient visits, with the most significant decline in the Ob-Gyn polyclinic that reached 50%. Several factors could cause this decline, including the suboptimal promotion of the hospital's leading programs, a suboptimal response from the customer service officers, specialist doctors who do not only work at “X” Hospital that causes priority clashes, unclear signboards at the hospital, an uncomfortable waiting room at the outpatient polyclinic, patients who often cancel the visits, faulty online registration, and no patient satisfaction measurement in the outpatient installation. These situations will eventually cause increasing operational costs. This study aimed to determine the factors that caused decreasing patient visits at the Ob-Gyn polyclinic of “X” Hospital. This research used questionnaires distributed to patients in the Ob-Gyn polyclinic totaling 135 respondents and google forms distributed to the employees of “X” Hospital. The collected data were processed using descriptive statistics. From the study results, the three main factors that caused the decreasing patient visits are the suboptimal promotion of the hospital's leading programs, the suboptimal response of the customer service officers, and the absence of patient satisfaction measurement at the outpatient installation.